2014
DOI: 10.1007/s11064-014-1493-x
|View full text |Cite
|
Sign up to set email alerts
|

Flavanonol Taxifolin Attenuates Proteasome Inhibition-Induced Apoptosis in Differentiated PC12 Cells by Suppressing Cell Death Process

Abstract: The proteasomal dysfunction and mitochondrial impairment has been implicated in neuronal degeneration. Taxifolin has antioxidant and anti-inflammatory effects. However, the effect of taxifolin on the neuronal cell death induced by proteasome inhibition has not been studied. Therefore, in the respect of cell death process, we assessed the effect of taxifolin on the proteasome inhibition-induced apoptosis in neuronal cell injury using differentiated PC12 cells. The proteasome inhibitors MG132 and MG115 induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In this study, similar results were also obtained in hepatic oxidative stress indicators after modeling with LPS. As an effective antioxidant [ 42 ], most of the antioxidant activity of DHQ had been confirmed in vitro or in therapy models [ 43 , 44 ]. Previous reports have indicated that the antioxidant effect of DHQ may act through binding of metal ions [ 43 ] and inhibiting enzymatic reactions [ 45 ], leading to free radical formation as well as inhibiting lipid peroxidation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, similar results were also obtained in hepatic oxidative stress indicators after modeling with LPS. As an effective antioxidant [ 42 ], most of the antioxidant activity of DHQ had been confirmed in vitro or in therapy models [ 43 , 44 ]. Previous reports have indicated that the antioxidant effect of DHQ may act through binding of metal ions [ 43 ] and inhibiting enzymatic reactions [ 45 ], leading to free radical formation as well as inhibiting lipid peroxidation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, taxifolin suppressed the development of oxidative stress in the lung tissue of cisplatin-treated animals. Studies also reported that taxifolin suppressed MDA production in a PC12 cell line [25] and that it provided protection against inflammatory-induced damage in the lung tissue in an experimental study by suppressing MPO activity [26]. No previous studies have investigated the effect of taxifolin on tGSH in the lung tissue or its effect on DNA oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior after the test, the rats in all groups randomly selected 30 rats (5) in each group, with 10 % chloral hydrate anesthesia in rats, with 2.5 % glutaraldehyde perfusion fixed phosphate buffer, quickly put to death and brain tissue of rats are extracted, isolated hippocampal tissue, will be isolated from the hippocampus to clean phosphate buffer, ultra-thin slicing machine slices after polymerization, observed by TEM to observe and record the value.…”
Section: Transmission Electron Microscope (Tem) Observationmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) believes that the loss of medullary sea and insufficiency of renal essence are the main pathogenesis of senile dementia [4] . It is certain that the pathogenesis of senile dementia is closely related to the generation of SPs [5] . Age spots are not solubility of plaques in the brain organization, its main composition is extracellular beta-amyloid, autopsy study found that patients with AD in AD patients in the body of Amyloid-beta (Aβ) 1-42 may also appear in the normal brain tissue, the protein in brain tissue of precipitation accumulated a large number of local space and converge into age spots, such change is brain tissue to combat AD cause related injury of a kind of brain tissue damage metabolic mechanism [6,7] .…”
mentioning
confidence: 99%